RFID-Enabled Smart Manufacturing: Real-Time Asset Tracking and Operational Workflow Optimization - Andrzej Paszkiewicz; Karol Siwiec; Bartosz Pawłowicz; Grzegorz Budzik; Maria Ganzha; Marcin Paprzycki (Tehnički Glasnik)
The article presents the possibility of implementing an RFID system to increase transport efficiency in both classic industrial environments and in infrastructure with a high level of automation. The proposed solution takes into account the possibility of installing RFID readers on poles, suspended ceilings, as well as in the floor of the storage and communication space. Thanks to its universal approach and scalability, it allows to increase the level of process automation, especially in SMEs. The implementation of the proposed system in modern factories will make it possible to track in real time the location of products and materials required for production and will have a positive effect on optimizing the flow of these objects within the production environment. Moreover, the implementation of this system is affordable for most enterprises.